Evolution of Learning Environment: A Review of Ubiquitous Learning Paradigm Characteristics - Zurainee Mohd Tahir; Haryani Haron; Jasber Kaur Gian Singh (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper performed literature analysis for evolution of learning environment focusing on a new learning paradigm which is known as ubiquitous learning environment. This paper also intend at providing specific information about ubiquitous learning concepts and the criteria that needed in the future research.  It begins by briefly describing the evolution of learning environment with the comparison for each of the learning paradigms. Finally, the definition of ubiquitous learning and the comparison of characteristics in ubiquitous learning paradigm are also compared and discussed to further enhance the understanding of ubiquitous learning concept. As a conclusion these paper providing a basis foundation for novice researcher that interested in exploring ubiquitous learning environment area.